2009
DOI: 10.1007/s00167-009-0952-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of plain radiography, computed tomography, and magnetic resonance imaging in the evaluation of bone tunnel widening after anterior cruciate ligament reconstruction

Abstract: Bone tunnel widening poses a problem for graft fixation during revision anterior cruciate ligament (ACL) reconstruction. Large variability exists in the utilization of imaging modalities for evaluating bone tunnels in pre-operative planning for revision ACL reconstruction. The purpose of this study was to identify the most reliable imaging modality for identifying bone tunnels and assessing tunnel widening, and specifically, to validate the reliability of radiographs, MRI, and CT using intra- and inter-observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 28 publications
1
93
0
1
Order By: Relevance
“…Agreement of the measurements on radiographs was poor in our study. This is in accordance with previous studies [24,32]. The poor agreement on radiographs is foremostly explained by the often barely discernible tunnel center on post-operative radiographs (Fig.…”
Section: Femoral Tunnelsupporting
confidence: 92%
“…Agreement of the measurements on radiographs was poor in our study. This is in accordance with previous studies [24,32]. The poor agreement on radiographs is foremostly explained by the often barely discernible tunnel center on post-operative radiographs (Fig.…”
Section: Femoral Tunnelsupporting
confidence: 92%
“…Segawa et al [30] suggested that the femoral tunnel angle was significantly more acute in patients displaying femoral tunnel enlargement than in patients without femoral tunnel enlargement. Graft placement is challenging during revision ACL reconstruction particularly when bone loss is present [20]. The mean femoral graft bending angle in group I was larger, and the mean femoral tunnel-shaft axis angle in group I was smaller than the mean AM and PL femoral graft bending angle in group II.…”
Section: Discussionmentioning
confidence: 95%
“…Tunnel widening was determined using standardized CT scans [27,32]. The measurements of tibial tunnel width at a level of 10 mm below the articular surface were taken Fig.…”
Section: Demographic and Baseline Disease Characteristicsmentioning
confidence: 99%